PUBLIC POLICIES, BUSINESS ENVIRONMENT, AND ECONOMIC GROWTH IN DEVELOPING COUNTRIES - MINH QUANG DAO (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, ECONOMICS & MANAGEMENT, 2013)
This paper examines the impact of public policies and the business environment on economic growth in developing countries. Based on data from the World Bank for the 2000-2011 period and a sample of fifty-six developing economies we find that the growth rate of per capita GDP is dependent on a country’s economic management, its structural policies, its policies for social inclusion and equity, the number of procedures to build a warehouse, and the cost of starting a business as a percent of per capita income. We observe that the coefficient estimates of two explanatory variables, namely, the structural policies average and the number of procedures to build a warehouse, do not have their expected sign, possibly to the collinearity between the structural policies average variable and the economic management average variable as well as the policies for social inclusion and equity average variable. On the other hand, the cost of starting a business as a percent of per capita income is not significant using the t-test. We suspect that this is also due to the collinearity between this variable and three policies variables. Statistical results of such empirical examination will assist governments in developing countries focus on appropriate policies dealing with economic management, those of a structural nature, and those for social inclusion and equity while recognizing the importance of a good business environment in order to foster economic growth.